(untitled) (Journal of Tourism and Hospitality Education, 2019)
Ecotourism is a form of nature-based tourism. It is recognized as the sustainable alternative to the mass tourism and is executed to contribute to the protection and enhancement of various component of the environment. As environmental and cultural diversity are considered as the greatest assets to ecotourism, Nepal with high cultural and environmental diversity is prime destinations for ecotourism and other forms of nature-based tourism. Ecotourism contributes to the conservation of biodiversity as a primary source of internal funding in the protected areas. Researches on the aspects of ecotourism in Nepal were focused towards potentiality evaluation, impact assessment and the impact of climate change including others. Despite the significance of ecotourism in the Nepalese economy, research on governance aspects of ecotourism is limited. This article aims to analyze the role of government in ecotourism development in Nepal through policy-based approach. Beside this, data of visitation in the protected areas was evaluated. Tourist number in the protected area was observed to increase in a gradual fashion in response to the growing number of tourists visiting Nepal. Tourism policies of government primarily focus to increase the number of tourists in the country and fail to recognize tourism carrying capacity and environmental implication. Different tourism and other sectoral policies attempt to cover the issues of ecotourism, but, ecotourism specific policy is yet to be drafted. In addition to this, the tourism aspect is addressed by the species conservation action plan for species-level conservation within the country. In all, nine action plans reviewed, the provisions relating to tourism were found to be too general, most of them acknowledging ecotourism as a source of conservation funding but failed to define species-specific policy. A similar trend can be observed in the protected area management plan excluding the Chitwan and Banke National Park. Further study on the implementation status and formulation of new policy to address the holistic issues of ecotourism is an urgent requirement.